Humanities, Medicine and Art: Ten Year of Experience and Next Challenges - Andrade, Luciana; Mallet, Ana Luisa Rocha; Kestenberg, David; Geovanini, Fátima Cristina Melo (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2022)
This article presents the ten-year work of the Humanidades, Medicina e Arte group, which used literature and other arts as instruments for reflection and writing carried out by undergraduate students. Subsequently, other practices of Narrative Medicine were included in the meetings and in some disciplines. To evaluate the impact of this work, we carried out a study on the perception of students after participating in these activities. The results revealed a positive impact on the participants. However, there are numerous challenges to expand the reach of the group in medical education.